MANIFESTATION OF SOCIETAL ATTITUDE TOWARDS THE SOCIAL WORKER’S PROFESSION IN LITHUANIA AND THE UKRAINE - Nemeikšienė, Virginija; Rūdytė, Kristina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper focuses on the issues of societal attitude towards the social worker’s profession. Aiming to reveal the societal attitude towards manifestation of the social worker’s profession in Lithuania and the Ukraine, a quantitative research method has been chosen, using a semi-standardised questionnaire. The research data analysis employed a non-parametric statistical method – Kruskal-Wallis test. The hypothesis raised at the beginning of the research has been partly proven: it is likely that society has no clear vision on what are the characteristics of the content of professional activities of a social worker. The answers of the respondents (N=784) suggest that they cannot exactly say what social work is; but understand where and with what kinds of people’s groups the staff can work. They do not single out professional competences; however, they name the knowledge, abilities which are required for a social worker. They understand the values which are not attributed to general values but rather particularly oriented to a client, and know real material condition of a social worker, i.e. that this job is low paid.